Immunosuppressive Drug-Associated Adverse Event Profiles in De Novo Kidney Transplant Recipients Receiving Everolimus and Reduced Tacrolimus Doses. Issue 6 (December 2020) - Miranda, Tamiris A.; Felipe, Claudia R.; Santos, Renato H. N.; Medina Pestana, Jose O.; Tedesco-Silva Junior, Helio
Abstract : Background: The safety of immunosuppressive regimens is influenced by the induction agent, maintenance drug combination, and prophylactic strategy for cytomegalovirus (CMV) infection. Herein, this safety analysis compares rabbit antithymocyte globulin (r-ATG) or basiliximab (BAS) combined with everolimus (EVR) versus BAS combined with mycophenolate sodium (MPS) in kidney transplant recipients receiving tacrolimus, prednisone, and preemptive CMV therapy. Methods: In this single-center, prospective, randomized study, adverse events (AEs), serious AEs (SAEs), viral infections, laboratory abnormalities, dose reductions, and temporary or permanent discontinuation of the immunosuppressant were compared among patients receiving r-ATG/EVR (n = 85), BAS/EVR (n = 102), and BAS/MPS (n = 101). Results: A total of 2741 AEs and 344 SAEs were observed. There were no differences in the proportion of patients with at least one AE (96% versus 98% versus 96%, respectively; P > 0.05). The proportion of patients with at least one SAE was highest in the BAS/MPS group (33% versus 48% versus 69%, respectively; P < 0.05). This difference was due primarily to a high incidence of CMV infection in the BAS/MPS group (4.7% versus 10.8% versus 37.6%, respectively). The incidence of mild/moderate abnormalities in creatinine, cholesterol, and triglyceride levels was higher in both EVR groups. The cumulative freedom from dose reduction or treatment discontinuation due to an AE was higher in both EVR groups than in the BAS/MPS group (89.2% versus 92.8% versus 76.3%, respectively, P = 0.003). There was no difference in the incidence of biopsy-confirmed acute rejection (9.4% versus 18.6 versus 15.8%, respectively; P = 0.403). Conclusions: This analysis suggests that r-ATG induction combined with EVR is associated with a comparable incidence of acute rejection, lower incidence of CMV infection, and fewer changes in initial immunosuppressive regimen due to AEs in kidney transplant recipients receiving tacrolimus, prednisone, and preemptive CMV therapy. Abstract : Supplemental Digital Content is Available in the Text.